A conceptual framework of university of the future-domestic and international students’ perspective - Ahmad Dahlan, Abdul Rahman; Parvin, Sultana; Al Khudair, Rawan (Eclat Research Publication, 2016)
There is much discussion these days about the fundamental changes of universities and higher education (HE). That is why they need to shape themselves the way of delivering methods as well as whole model of conducting their services because of that we propose a model for the university of the future based on Business Model Canvas. This is mainly a conceptual paper where literature reviews were conducted and initial model of University-of-the-Future (UotF) was established; and surveys based on structured questionnaire were conducted involving 30 participants on their preference of future universities. Also we make interview with some of the participants of those thirty to find out several factors like value proposition, key resources, key partners, key activities, and so on. After this survey and interview, we propose a model of future universities where we find some important points which can make universities more dynamic and successful such as MOOC, hologram, website for discussion, involving industry leader to make curriculum, those are crucial factors which universities must need to adopt. Moreover, there are some other points which need more attention like flexible curriculum, part-time jobs within universities in different forms, and selling research products. Even though we find some important points, this paper is not enough to get the whole idea about UotF as we only focus on two customer segments: undergraduate and post graduate. Also, our survey participants are limited in numbers and most of them are undergraduates’ students. Still it is a great joy for us that people are thinking universities need to be changed and it should give more importance on collaboration with industry and other parts of the world.